2012
DOI: 10.1118/1.3679858
|View full text |Cite
|
Sign up to set email alerts
|

Can volumetric modulated arc therapy with flattening filter free beams play a role in stereotactic body radiotherapy for liver lesions? A volume-based analysis

Abstract: RapidArc plans optimized using FFF were dosimetrically equivalent to those optimized using FF beams, showing the feasibility of SBRT treatments with FFF beams. Some improvement in healthy tissue sparing was observed when using the FFF modality due to the different beam's profile. The main advantage was a considerable reduction of beam-on time, relevant for SBRT techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 22 publications
3
60
0
Order By: Relevance
“…Although no modeling details presented, successful modeling of FFF beam in other TPS had also been exemplified. [13] It seems that handling unflattened beams in today's TPS is no longer a problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no modeling details presented, successful modeling of FFF beam in other TPS had also been exemplified. [13] It seems that handling unflattened beams in today's TPS is no longer a problem.…”
Section: Discussionmentioning
confidence: 99%
“…[8] During the past years, feasibility of treating various cancers including prostate, lung, larynx, chest wall, and esophagus using unflattened beams have been reported. [910111213141516] Also exclusive use of a linear accelerator in FFF mode in 3D CRT planning has also been reported to be feasible. [17] From all these published results, a reduced beam on time (BOT) and comparable plan quality seem to have been confirmed for VMAT plan with unflattened beams.…”
Section: Introductionmentioning
confidence: 99%
“…Table III. FFF beams (11). The main advantage was a considerable reduction of beam on time, relevant for SBRT techniques (11). In our study, the treatment delivery efficiency is quantified by lesser BOT.…”
Section: Technology In Cancer Research and Treatment 2014 March 17 Epumentioning
confidence: 99%
“…6X_IMRT and 6F_IMRT reduces the V 10% volumes in the OARs especially in heart (20% reduction), lungs (40% reduction), liver (64.9% reduction), kidneys (62.5% reduction) compared to Rapid Arc therapy as shown in Figure 3. Table III. FFF beams (11). The main advantage was a considerable reduction of beam on time, relevant for SBRT techniques (11).…”
Section: Technology In Cancer Research and Treatment 2014 March 17 Epumentioning
confidence: 99%
“…Since flattening filter is not used in the photon beam, the dose rate can be increased by two to four times of the conventional treatment so that the delivery time can be faster. Reggiori et al (14) have reported considerable reductions in the treatment time, along with some improvement in healthy sparing tissue, by using the high‐dose rate FFF beams in VMAT‐based lung SBRT.…”
Section: Introductionmentioning
confidence: 99%